2015
DOI: 10.1039/c5cp01383f
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast primary processes of the stable neutral organic radical, 1,3,5-triphenylverdazyl, in liquid solution

Abstract: Femtosecond spectroscopy with hyperspectral white-light detection was used to elucidate the ultrafast primary processes of the thermodynamically stable organic radical, 1,3,5-triphenylverdazyl, in liquid acetonitrile solution at room temperature. The radical was excited with optical pulses having a duration of 39 fs and a center wavelength of 800 nm thereby accessing its energetically lowest electronically excited state (D1). The apparent spectrotemporal response is understood in terms of an ultrafast primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Furthermore, the electronic coupling also has no strong influence on the IC rate as is obvious when looking at the coupling in Table 1 which covers a factor of six on going from of 1 + to 3 + . Such a thermalisation may be simulated by the Sulzer-Wieland formalism 53-55 as has recently been done in case of verdazyl radicals by Voehringer et al 56 However, this model is based on a number of assumptions concerning the potential surfaces involved which prompted us to calculate the cooling of spectra explicitly based on the ground and excited state potentials as given in Fig. 0.3-0.5 ps (MeCN and DCM) to ca.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the electronic coupling also has no strong influence on the IC rate as is obvious when looking at the coupling in Table 1 which covers a factor of six on going from of 1 + to 3 + . Such a thermalisation may be simulated by the Sulzer-Wieland formalism 53-55 as has recently been done in case of verdazyl radicals by Voehringer et al 56 However, this model is based on a number of assumptions concerning the potential surfaces involved which prompted us to calculate the cooling of spectra explicitly based on the ground and excited state potentials as given in Fig. 0.3-0.5 ps (MeCN and DCM) to ca.…”
Section: Introductionmentioning
confidence: 99%
“…By doing a transient absorption experiment on Verdazyl, exciting the D 1 ← D 0 transition using 800 nm light, Weinert et al observed that after a c. 500 fs induction period (which they deduce to possibly provide an upper limit on the D 1 lifetime), the transient absorption spectra decay display a time-dependent peak position which shifts to higher energy with time, and that the time traces display non-exponential relaxation back to zero. [76] They thus interpreted this as the signature of a rapid internal conversion back to the ground state, producing a vibrationally hot ground state. Thus, they used the Sulzer-Wieland formalism (equations ??…”
Section: Applicationsmentioning
confidence: 99%
“…[73] Nonetheless, the paper presents a remarkably detailed investigation of the relaxation of the Verdazyl chromophore. [76] but with the D 1 ← D 0 transition scaled, as was needed for direct comparison. Time delays are 500 fs (brown), 1 ps (red), 2 ps (orange), 3 ps (green), 5 ps (light blue), and 10 ps (dark blue).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This assignment is corroborated by the transient absorption profile, which resembles the absorption of the triphenylverdazyl radical. [20,21] The latter compound is an open-shell system with an additional carbon compared to TTC, giving rise to a six-membered ring and a non-planar and non-aromatic NNCNN sequence with a delocalized unpaired electron, as also present in ro-TTCC. Several studies have pointed out the close relation of these radicals.…”
mentioning
confidence: 99%